A novel approach in the diagnosis and follow-up of sarcoidosis - Balcı, Aydın; Aydın, Suphi (Journal of Surgery and Medicine, 2020)
Aim: Sarcoidosis is characterized by the presence of non-caseous granulomas that can involve all organs, especially the lungs and mediastinal lymph nodes. No biomarker investigated in recent years appears to be specific for sarcoidosis. We aimed to investigate and evaluate the relationship between neutrophil-lymphocyte ratios (NLR), platelet-lymphocyte ratios (PLR), monocyte-lymphocyte ratios (MLR), eosinophil-lymphocyte ratios (ELR), and blood count parameters in sarcoidosis patients. Methods: A total of 150 individuals comprising 97 sarcoidosis patients, and 53 controls, were included in the study. The data were recorded retrospectively. Chest X-ray findings were analyzed with regards to age, gender, body mass index, modified medical research concept (MMRC) dyspnea scale and respiratory function parameters. Blood count, NLR, PLR, MLR, eosinophil/basophil ratio (EBR) were evaluated in patients with sarcoidosis. Results: Hemoglobin (g/dl) and lymphocyte count (103 /UL) values were significantly lower in sarcoidosis patients, while red blood cell distribution width standard deviation (RDW SD) (fl), neutrophil count (103 /UL), monocyte count (103 /UL), basophil count (103 /UL), NLR, PLR, MLR values were significantly higher compared to the control group. However, platelet (103 /UL), MPV and EBR values were similar. Conclusion: Our study showed that MLR value, which was not previously used in sarcoidosis patients, is an important biomarker in the diagnosis of sarcoidosis, just as NLR.